Serologic Screening for Smooth Brucella sp. in Wild Animals in Brazil - Silva Batista, Talita Gomes da; Fornazari, Felipe [UNESP]; Joaquim, Samea Fernandes [UNESP]; Latosinski, Giulia Soares [UNESP]; Teixeira, Carlos Roberto [UNESP]; Langoni, Helio [UNESP] (Wildlife Disease Assoc, Inc, 2019)
Antibodies against smooth Brucella were investigated in serum samples of 526 free-ranging mammals (21 species) in Brazil. All animals were seronegative, which indicated low-level exposure to these bacteria.